School choral eisteddfodau in the Polokwane Cluster of circuits in the Capricorn District of Limpopo Province, South Africa : an assessment of racial participation - Vermeulen, Dorette (University of Pretoria, 2015)
Dissertation (MMus)--University of Pretoria, 2014.